Sexual Assault During and After Separation or Divorce in Rural Ohio, 2003-2004 - DeKeseredy, Walter S. ([Verlag nicht ermittelbar], 2008)
This qualitative study explored incidents of sexual assault of women by former husbands or cohabitants and the link to male peer support for sexually aggressive men in rural Ohio. Sexual assault was defined as unwanted sexual contact, sexual coercion, attempted rape, or rape. A series of screening questions were asked to determine a respondent's eligibility for inclusion in the study. The main criteria were being aged 18 or older and having ever had any type of unwanted sexual experience when they wanted to end, were trying to end, or after they had ended a relationship with a husband or live-in male partner. If they met the selection criteria, the women were invited to a semi-structured face-to-face interview at a time and place of their choosing. Between February 2003 and July 2004, 43 women were interviewed. The interviews included several demographic questions such as income, level of education, marital status, length of the relationship, and how long the respondent had lived in the area. Other questions asked about the unwanted sexual experiences, social support networks, and male pornography use.